A DEM analysis of geomembrane-lined landfill subject to vertical loading - Hou, Juan; Li, Hao; Liu, Lei; Wang, Shihan; Teng, Yuyang; Bao, Shifen (Geotextiles and geomembranes, 2021)
Particle flow code in three dimensions (PFC3D) is used to investigate the bearing capacity and mechanism of a geomembrane-lined landfill under construction loading. The soils and the geomembranes are simulated by numerous balls and parallel bond, respectively. The initial states and loading processes of geomembrane-lined soil are simulated by PFC3D method. The displacement vector diagram, the velocity vector diagram, the stress and the porosity of soil were analyzed using the numerical models. The simulation results demonstrate that the geomembranes keep the underneath soil particles from being displaced under the applied load and can distribute the load uniformly over a wider area. The interface between soil particles and geomembranes, the displacement vector, the contact force and the deformation of the geomembranes are also analyzed. The results showed that the vertical loading affect strength-strain behavior of geomembranes. The contribution of radial displacements on strain and, consequently, the stress crack and potential failure mechanism of geomembranes were analyzed.